How are firm's wages and prices linked: Survey evidence in Europe - Martine Druant; Silvia Fabiani; Gábor Kézdi; Ana Lamo; Fernando Martins; Roberto Sabbatini (Magyar Nemzeti Bank, 2012)
This paper presents new evidence on the patterns of price and wage adjustment in European firms and on the extent of nominal rigidities. It uses a unique dataset collected through a firm-level survey conducted in a broad range of countries and covering various sectors. Several conclusions are drawn from this evidence. Firms adjust wages less frequently than prices: the former tend to remain unchanged for about 15 months on average, the latter for around 10 months. The degree of price rigidity varies substantially across sectors and depends strongly on economic features, such as the intensity of competition, the exposure to foreign markets and the share of labour costs in total cost. Instead, country specificities, mostly related to the labour market institutional setting, are more relevant in characterising the pattern of wage adjustment. The latter exhibits also a substantial degree of time-dependence, as firms tend to concentrate wage changes in a specific month, mostly January in the majority of countries. Wage and price changes feed into each other at the micro level and there is a relationship between wage and price rigidity.
Keywords: D21; E30; J31; 330; survey; wage rigidity; price rigidity; indexation; institutions; time dependent